The hostile environment : students who bully in school - Carter, Susan (Lanham, Maryland : Lexington Books, 2015)
Examines the latest psychological and educational research providing evidence that anti-bullying programs and school-based interventions lack intensity and a strong behavioral focus. This book includes information on characteristics and risk factors of bully perpetrators and victims, current laws and legal aspects of bullying, vulnerable populations of students such as students with disabilities and who are LGBT, and cyberbullying. Barriers to successful implementation of anti-bullying programs and societal problems are discussed. In light of recent state and federal anti-bullying legislation, now is an opportune time to examine the laws and evidence base with the intent of initiating significant changes in schools to interrupt the persistent cycle of bullying. A bold and new interdisciplinary model integrating teacher contracts and policies, increased mental health provisions for children and families, and communication between law enforcement and pediatricians is called for to change what has become a worldwide public health concern, a substantial disruption to the educational process, and a hostile environment in schools and communities--Back cover.
Introduction: Problems associated with the study of bullying -- Persistence of the bullying problem in schools -- The hostile environment : legal aspects of school bullying -- Characteristics, correlates and risk factors of bully perpetrators -- Cyberbullying and relationship between bullying and mental health -- Bully-victims, victims and students most vulnerable to bullying -- Implications for schools : practices for consideration and future research -- Conclusion: What the evidence suggests.
Includes bibliographical references (pages 101-122) and index.
Keywords: Bullying in schools; School violence; EDUCATION / Behavioral Management; EDUCATION / Educational Policy & Reform / School Safety; EDUCATION / Philosophy, Theory & Social Aspects; EDUCATION / Violence & Harassment